The utilization and potential of solar energy in Somalia: Current state and prospects - Samatar A.M.; Mekhilef S.; Mokhlis H.; Kermadi M.; Diblawe A.M.; Stojcevski A.; Seyedmahmoudian M. (Elsevier Ltd, 2024)
In Somalia, access to electricity impedes economic growth and sustainable development. Despite having abundant solar energy potential due to its location near the equator, the utilization of solar energy in Somalia is still limited due to unfamiliarity, lack of energy awareness, high initial costs, and lack of infrastructure. The Somali government has established the National Regulatory Authority and set a goal to increase energy access from 15 to 45% by 2024 through the National Development Plan (NDP) 9th (20202024). This study aims to analyze and verify the utilization and potential of solar energy in Somalia to understand opportunities and challenges and identify suitable areas and technologies for development. This study explores Somalia's energy profile and the potential for harnessing solar energy. The installed photovoltaic capacity was found to be 41 MW and contributed 11.9% of the total electricity generation. A case study on a solar power microgrid system in Bacadweyene, Somalia, is also presented. The research provides valuable information on the status of the utilization and potential of solar energy in Somalia and aligns with the NDP 9th. The results can serve as a scientific framework for companies and researchers to seek feasible strategies for future investment in solar energy applications in Somalia. 2023 The Authors